Pengaruh Budaya Organisasi, Knowledge Management dan Motivasi Kerja terhadap Kinerja Pegawai Badan Kepegawaian Daerah Provinsi Sulawesi Tenggara - Andi Rachmat Boeston; Nurwati Nurwati; Wahyuniati Hamid (Pascasarjana Universitas Halu Oleo, 2023)
The purpose of this study was to examine and examine the influence of organizational culture, knowledge management and work motivation on the performance of the Regional Personnel Agency of Southeast Sulawesi Province. The analytical model used is multiple linear regression analysis. The number of respondents in this study were 100 respondents. The research sample determination method used the census method where all civil servants at the Regional Personnel Agency of Southeast Sulawesi Province were used as research respondents.The results of the study found that: 1) organizational culture, knowledge management and work motivation simultaneously have a positive and significant effect on employee performance; 2) organizational culture partially positive and significant effect on employee performance; 3) knowledge management partially has a positive and significant effect on employee performance; 4) work motivation partially has a positive and significant effect on employee performance.